2014
DOI: 10.1155/2014/503194
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Adsorption: Experimental Investigation and CFD Reactor Model Validation

Abstract: The National Energy Technology Laboratory is investigating a new process for CO 2 capture from large sources such as utility power generation facilities as an alternative to liquid amine based adsorption processes. Many of these advanced dry processes are based upon sorbents composed of supported polyamines. In this analysis, experiments have been conducted in a laboratory-scale fluidized bed reactor and compared to CFD reactor predictions using kinetics obtained from TGA tests. Batch experiments were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The central core comprised about 15% of the mass inventory; therefore, a defluidized central core was considered the most likely cause leading to this low pressure differential. In a computational fluid dynamic study of the hydrodynamics with this distributor configuration, but no internal coils, some stagnation was reported in the central core region; however, the Δ P was 28% lower than the expected weight of the bed. A calculation of the volume between the coils suggests that this would be sufficient to explain reduced pressure differential, representing 14% of the volume.…”
Section: Resultsmentioning
confidence: 78%
“…The central core comprised about 15% of the mass inventory; therefore, a defluidized central core was considered the most likely cause leading to this low pressure differential. In a computational fluid dynamic study of the hydrodynamics with this distributor configuration, but no internal coils, some stagnation was reported in the central core region; however, the Δ P was 28% lower than the expected weight of the bed. A calculation of the volume between the coils suggests that this would be sufficient to explain reduced pressure differential, representing 14% of the volume.…”
Section: Resultsmentioning
confidence: 78%
“…Breault et al. compared results of the 3D non‐isothermal multiphase CFD simulation by using kinetics obtained from thermogravimetric analysis (TGA) with batch experiments conducted by flowing a mixture of CO 2 and N 2 gas and vapor through a fluidized bed, and found that the time duration of CO 2 capture decreased with increasing gas flow . Recently, Breault et al.…”
Section: Theoretical Studiesmentioning
confidence: 99%